Tourism boycotts and animosity: A study of seven events - Yu, Qionglei; McManus, Richard; Yen, Dorothy A.; Li, Xiang (Robert) (Annals of tourism research, 2020)
The impacts of tourism boycotts on a destination's tourist economy can be vast, yet few studies have examined such events. This paper explores the effects of tourism boycotts by analysing seven events involving Chinese tourism boycotts during the past decade. The findings show that boycotts can significantly decrease visitor numbers. Also, non-political animosity boycotts and political animosity boycotts differ in their intensity and impact; the former are found to exert immediate short-term impacts, whereas the latter tend to have enduring effects. These results are based on local projection techniques using narratively identified boycott events and are robust to several specifications. This paper highlights tourism boycotts as a key risk factor in destination management. •Provide a framework explaining boycott motivations, purposes, actions, and impact•Demonstrate tourism boycott's impact on visitor numbers, beyond visitor intention•Boycotts associated with political animosity have a profound and enduring effect•Describe boycott behaviour specific to the Chinese tourism market